Analisis Kelayakan Teknis dan Finansial Usaha Agroindustri Bakso Ikan (Studi Kasus pada Home Industry Chikanos Food Kendari) - Kadang, Tika Evita; Sinaini, La (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2018)
This study aims to identify the technical and financial feasibility of fish meatball agroindustry Home Industry Chikanos Food. This research is a case study on Chikanos Food fish meatball business. The object of research is determined purposively because legally this business has legality and has been operating for 5 (five) years. The results showed that from the results of technical aspects analysis, Fish Industry Home Industry agroindustry, Chikanos Food can be said to be feasible, both from production capacity, adequate facilities and infrastructure, and production process technology that has been running for 5 (five) years. Financially this business is feasible to continue, where the NPV value is greater than zero, which is Rp.136,923,035, the IRR is greater than bank interest which is 42.5 percent, and Net B / C is greater than one, which is 3.24. The results of the sensitivity analysis show that if there is a 10 percent increase in costs with fixed income or a decrease in revenue of 10 percent with a fixed cost, then this business remains profitable. If a cost increase of 10 percent occurs, the NPV value is greater than zero, which is Rp. 36.417175; IRR is greater than OCC, which is 15.27 percent; and NBCR is greater than one, which is 1.35. If there is a decrease in revenue of 10 percent, the NPV value remains positive, namely Rp. 22,736,802; IRR is greater than OCC, which is 12.41 percent; and NBCR is greater than one, which is 1.23.